2020
DOI: 10.1002/gj.3806
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and petrogenesis of the volcanic rocks from the middle Sanjiang Tethys Orogen, SW China: Implications for the Sanjiang Paleo‐Tethyan evolution

Abstract: The volcano‐sedimentary sequences from the Weixi belt provide significance for the Sanjiang Paleo‐Tethys evolution. This manuscript constrains the ages of volcano‐sedimentary sequences by LA‐ICPMS U–Pb, including bimodal volcanics (245.0–244.0 Ma) from Pantiange Formation, trachyandesite–basaltic andesite (234 ± 2.0 Ma) from Cuiyibi Formation, high silica subalkaline rhyolite (221 ± 1.4 Ma) from Waigucun Formation and Early Jurassic high silica subalkaline rhyolite (184 ± 2.2 Ma). The volcanics show various Hf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 67 publications
0
1
0
Order By: Relevance
“…and Griesbachian postextinction interval (Post-E.). Conodont stratigraphy has been undertaken at all the investigated sections where Hindeodus parvus , whose first appearance datum (FAD) defines the base of the Triassic (Yin et al 2001), typically occurs near the base of the microbialites facies, and the Isarcicella staeschei biozone occurs above the microbialite interval (Yang et al 1999; Richoz 2006; Sudar et al 2008; Jiang et al 2014; Forel et al 2015). Furthermore, in most Permian/Triassic boundary successions, the microbialites also have irregular contact with the underlying skeletal packstone, which marks the end-Permian mass extinction horizon (Payne et al 2007; Chen et al 2009; Jiang et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…and Griesbachian postextinction interval (Post-E.). Conodont stratigraphy has been undertaken at all the investigated sections where Hindeodus parvus , whose first appearance datum (FAD) defines the base of the Triassic (Yin et al 2001), typically occurs near the base of the microbialites facies, and the Isarcicella staeschei biozone occurs above the microbialite interval (Yang et al 1999; Richoz 2006; Sudar et al 2008; Jiang et al 2014; Forel et al 2015). Furthermore, in most Permian/Triassic boundary successions, the microbialites also have irregular contact with the underlying skeletal packstone, which marks the end-Permian mass extinction horizon (Payne et al 2007; Chen et al 2009; Jiang et al 2014).…”
Section: Methodsmentioning
confidence: 99%
“…There were two Paleo-Tethyan oceanic basins in the Weixi region during the Paleozoic (i.e., the Jinshajiang and Changning-Menglian Paleo-Tethyan oceanic basins). The Jinshajiang basin closed during the Early-Middle Triassic (Peng et al, 2008(Peng et al, , 2013Zi et al, 2012a;Yan et al, 2021), whereas the Changning-Menglian basin did not completely close until the Late Triassic (Yang et al, 2014a(Yang et al, , 2019Xin et al, 2018;Wang Q Y et al, 2023;Yin et al, 2023).…”
Section: Tectonic Setting Of the Weixi High-silica Granitoidsmentioning
confidence: 99%
“…Studies have suggested that the igneous rocks of the central Sanjiang orogenic belt were formed in association with the Jinshajiang Paleo-Tethys; i.e., the Early Triassic volcanic rocks were a response to the closure of the Paleo-Tethys, whereas the Middle Triassic volcanic rocks were formed by continent collision along the Jinshajiang suture zone (Zi et al, 2012a, b, c;Wang et al, 2014). The collision model is based mainly on the presence of Middle Triassic bimodal volcanic rocks (Zi et al, 2012a;Yan et al, 2021). However, a suite of andesitic rocks has been identified in the Weixi area, which provides robust evidence that the Middle Triassic volcanic rocks comprise andesite, basalt, dacite, and rhyolite (Yin et al, 2023).…”
Section: Tectonic Setting Of the Weixi High-silica Granitoidsmentioning
confidence: 99%